Demographic Characteristics and Autopsy Findings by Origin of Deaths due to Firearm Injury: Analytical Research - Ekinci, Ecesu; Balcı, Yasemin; Çallak, Füsun; Anolay, Nurettin Nezih (The Bulletin of Legal Medicine, 2023)
Objective: Determining the origins of deaths due to gunshot wounds is an important problem in terms of forensic medicine. In this study, it was aimed to retrospectively examine the deaths due to gunshot wounds that were autopsied between 2013 and 2020. Method: Age, gender, place of death, type of weapon used, origin, entry area, number of entries, shooting distance, toxicological examination results were recorded and statistical analyzes were made. Results: 85.5% (n:218) of the cases were male, 14.5% (n:37) were female, and the rate of suicide and accidental injuries was higher in men than in women, and the rate of being a victim of homicide in women was higher than men (P <0.001). While the death rate due to accidental injury was higher in the group aged 24 years and younger than the other age groups, the death rate due to injury caused by suicide in the group aged 65 and over was higher than the other age groups (P<0.01).Suicide-origin firearm injuries are higher in homes and attachments, homicide-origin firearms injuries are higher in closed spaces outside the home than in other crime scenes (P<0.001).Rifle was used mostly in accidental and suicide origin firearm deaths, and pistol was used mostly in murder-origin firearm deaths (P<0.001). Conclusion: It is thought that the demographic characteristics of the cases and autopsy findings will guide the members of the judiciary and forensic medicine specialists in determining the origins of the cases.